Результаты изучения морозостойкости озимой мягкой пшеницы - M. M. Ivanisov; E. V. Ionova (Зерновое хозяйство России, 2018)
The study results of frost tolerance of winter soft wheat The article gives the study results of frost tolerance of winter soft wheat varieties and lines in three research centers, i.e. ARRIGC named after I.G. Kalinenko, KRIA named after P.P. Lukiaynenko, DZRIA. During the study three methods of estimation of plant tolerance to low temperatures have been used, such as frosting of plants, grown in the seedling boxes; Donskoy method (in plastic bags); estimation of plant tolerance on the shelves. At -190C the plant preservation ranged from 42.4% to 91.5%. The variety ‘Don 107’ showed a true high frost tolerance. The varieties ‘Don 107’(83.8%), ‘Donskaya bezostaya’ and ‘Asket’(78.1%) showed the best plant preservation at -200C. The varieties ‘Don 107’(83.8%), ‘Donskaya bezostaya’ and ‘Asket’(78.1%) showed better plant preservation while using the Donskoy method. The plant preservation of the variety ‘Tarasovskaya 29’, grown on the shelves was 16.7%. The samples ‘260/09’(2.6%), ‘Admiral’(6.8%), ‘Lilit’(9%) and ‘Tanya’(9.8%) could preserve only 10% of plants. The varieties ‘Don 107’(64.1%) and ‘Donskaya bezostaya’(54.7%) could preserve more than 50%. After the research all studied samples were divided into three groups of tolerance: with high frost tolerance (‘Don 107’, ‘Donskaya bezostaya’, ‘Asket’), with average frost tolerance (‘Kapitan’, ‘Izyuminka’, ‘Krasa’, ‘Ermak’, ‘Krasa Dona’, ‘Admiral’, ‘Donskaya lira’) and with low frost tolerance (‘Lidiya’, ‘Lilit’, ‘Kaprizulya’, ‘Tanya’ and the lines ‘260/09’, ‘727/11’).